Correlation : Anatomical Variations of Nasal Cavity and Paranasal Sinuses and the Quality of Life Based on SNOTT-22 Score - Rani Rahmawati (Saintika Medika, 2021)
This study aims to determine the correlation between the anatomical variations of nasal cavity and paranasal sinuses and the quality of life based on SNOT-22 score in the patients who underwent paranasal sinuses CT scan. The samples are 36 patients with age ≥ 18 years. The method is Chi Square test / Fisher's test and Spearman’s rho test. The results showed that anatomical variations of the nasal cavity and paranasal sinuses from most of the patients who underwent paranasal sinuses CT scan had septal deviation n = 29, p = 0.007 (p <0.05) and concha bullosa n = 15, p = 0.029 (p <0.05). There was a significant correlation between total anatomical variation and quality of life based on SNOT-22 score in the patients who underwent paranasal sinuses CT scan p = 0.025 (p <0.05). There was no correlation between the anatomical variations of frontal cells, agger nasi cells, ethmoid bulla, uncinate process and haller cells and the quality of life based on SNOT-22 score in the patients who underwent paranasal sinuses CT scan.